Provider knowledge and perceptions following an integrated simulation training on emergency obstetric and neonatal care and respectful maternity care: A mixed-methods study in Ghana. (June 2020) - Afulani, Patience A.; Dyer, Jessica; Calkins, Kimberly; Aborigo, Raymond A.; Mcnally, Brienne; Cohen, Susanna R.
Abstract: Introduction: Little is known about the effect of integrating respectful maternity care into clinical training programs. We sought to examine the effectiveness of an integrated simulation training on emergency obstetric and neonatal care and respectful maternity care on providers' knowledge and self-efficacy, and to asess providers' perceptions of the integrated training. Methods: The project was piloted in East Mamprusi district in Northern Ghana. Forty-three maternity providers were trained, with six participants trained as Simulation Facilitators. Data are from self-administered evaluation forms (with structured and open-ended questions) from all 43 providers and in-depth interviews with 17 providers. We conducted descriptive quantitative analysis and framework qualitative analysis. Results: Provider knowledge increased from an average of 61.6% at pre-test to 74.5% at post-test. Self-efficacy also increased from an average of 5.8/10 at pretest to 9.2/10 at post-test. Process evaluation data showed that providers valued the training. Over 95% of participants agreed that the training was useful to them and that they will use the tools learned in the training in their practice. Overall, providers had positive perceptions of the training. They noted improvements in their knowledge and confidence to manage obstetric and neonatal emergencies, as well as in patient-provider communication and teamwork. Many listed respectful maternity care elements as what was most impactful to them from the training. Conclusions: Simulation and team-training on emergency obstetric and neonatal care, combined with respectful maternity care content, can enable health care providers to improve both their clinical and interpersonal knowledge and skills in a training setting that reflects their complex and stressful work environments. Our findings suggest this type of training is feasible, acceptable, and effective in limited-resource settings. Uptake of such trainings could drive efforts towards providing high quality safe, responsive, and respectful obstetric and neonatal care.